Diet and stones: Associations from a large, population-representative study of urolithiasis and renal colic-like pain symptoms in Poland - Jakub Szymanski; Przemyslaw Dudek; Pawel Rajwa; Wojciech Krajewski; Piotr Bryniarski; Katarzyna Krzanowska; Piotr Chlosta; Mikolaj Przydacz (PLoS ONE, 2026)
Introduction Urolithiasis and renal colic-like pain symptoms are prevalent conditions influenced by many factors, including diet. Regional assessments, particularly in culturally distinct areas, are essential for understanding specific risk patterns and for developing targeted public health strategies and educational programs. Therefore, the aim of this study was to identify associations between urolithiasis, renal colic-like pain symptoms, and diet, including body weight, in a representative sample of adult Poles. Methods A population-representative online survey of 10,029 adults was conducted using census-based quota sampling to ensure balanced representation by age, sex, and residence across all 16 Polish voivodships, including urban and rural areas. Results Normal-weight individuals had the lowest prevalence of urolithiasis and renal colic-like pain symptoms; overweight, obese, and underweight persons had higher prevalences (p < 0.001). Eighteen food items were linked to urolithiasis, with beef, legumes, soy, soda, coffee, and fast food found as independent predictors of urolithiasis. Nineteen foods were associated with renal colic-like pain symptoms, with processed meat, soy, legumes, fruit juices, soda, instant meals, and fast food identified as independent predictors of symptoms. Fast food showed the strongest effects, with daily consumption nearly tripling the risk of urolithiasis (OR=2.847; p = 0.001) and increasing renal colic-like pain symptoms by 64.5% (OR=1.645; p = 0.006) compared with no consumption of fast food. Conclusions This study provides the first comprehensive, population-based analysis of urolithiasis, renal colic-like pain symptoms, and dietary patterns in Central and Eastern Europe. Our findings demonstrate that both conditions are influenced by body weight and a range of dietary factors.